NILAI-NILAI MORAL DALAM NOVEL HABIBURRAHMAN EL SHIRAZY (TINJAUAN STRUKTURAL GENETIK) - Virry Grinitha (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2015)
ABSTRACT The objective of the research is to find out the moral values in Habiburrahman El Shirazy's Novels. The research was conducted using qualitative approach with descriptive method. The data were collected by analyzing, studying, and recording the document. The analysis and interpretation of the data indicate that first, moral values in novel's structure of the novels include human's perspective toward God, such as piety, devout, humble; human's perspective toward themselves such as honest, responsible, healthy, discipline, hard work, confident, logical, critical, creative, innovative, autonomous, curious; human's perspective toward human such as the awareness of their right and duty toward themselves and the others, the obedience of social norms, the appreciation of one's achievements and works, being polite and democratic, and human's perspective toward surroundings such as caring and admiring toward the beauty of nature created by God. Second, Moral values were analyzed through the author’s social background indicating the appearance of the novels. Third, moral values from the author's point of view in the novels include human's perspective toward God, themselves, the others, and surroundings. It is recommended that students should read the novels in order to find out the moral values in literary works.Keywords: moral values, novel, genetic structuralism ABSTRAK Tujuan penelitian ini ialah untuk mengetahui dan memberikan pemahaman yang lebih mendalam tentang nilai-nilai moral dalam novel karya Habiburrahman El Shirazy ditinjau dari struktural genetik. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi. Pengumpulan data menggunakan teknik analisis dokumentasi, pustaka, dan catat. Analisis interpretasi data menunjukkan (1) adanya nilai-nilai moral dalam struktur novel Ayat Ayat Cinta yang meliputi dimensi manusia dengan Tuhan yaitu religius, dimensi manusia dengan dirinya, dimensi manusia dengan manusia, yaitu sadar akan hak dan kewajiban diri sendiri dan orang lain dan dimensi manusia dengan lingkungan yaitu adanya keperdulian dan kekaguman terhadap keindahan alam yang diciptakan oleh sang pencipta, (2) nilai-nilai moral yang ditinjau dari sudut latar sosial pengarang yang mengkondisikan lahirnya novel Ayat Ayat Cinta; (3) nilai-nilai moral ditinjau dari sudut pandangan dunia pengarang dalam novel Ayat Ayat Cinta yang meliputi dimensi manusia dengan manusia, dimensi manusia dengan dirinya sendiri, dimensi manusia dengan manusia, dan dimensi manusia dengan lingkungan. Penemuan-penemuan membawa ke arah rekomendasi terhadap siswa agar membekali diri dengan berbagai bacaan penunjang lainnya untuk menemukan nilai-nilai moral yang terkandung dalam karya sastra.Kata kunci: Nilai-nilai moral, novel, struktural genetik